Sistem Informasi : Kunci Sukses Di Era Digital - Setiawan, Ilyas Aji; Pangestu, Adji; Hidayat, Awi; Alfizar, Aqmal; Fauzi, Fauzi (Journal of Computer Science and Information System(JCoInS), 2025)
As digital technology accelerates, information systems are the main foundation in helping organizations achieve success. These systems support businesses and institutions in adapting to technological innovations and maintaining competitiveness. This study reviews the importance of the role of information systems in digital transformation in various sectors, such as business, education, health, and government. With a qualitative approach through literature studies, this study evaluates the contribution of integrated information systems to operational efficiency, data-based decision making, innovation, and increased customer satisfaction. The results show that organizations that are consistent in developing modern information systems have advantages in terms of productivity and adaptive capabilities. This study also highlights the need for alignment between information system strategy and organizational goals for maximum impact. In the context of the digital economy, effective information management is a key differentiator. Therefore, investing in reliable and future-oriented information systems is a strategic need.